Group C+ particles: Enhanced flow and fluidization of fine powders with nano-modulation. (2nd November 2019) - Zhou, Yandaizi; Zhu, Jesse
Highlights: Group C + particles exhibit good flowability. Group C + particles could fluidize well with proper minimum fluidization velocity. Much higher bed expansion for Group C + particles when compared with Group A particles. Nanoparticle concentration possesses an optimum value of 0.5–1%. Optimum surface coverage is around 10–20%. Abstract: The main challenge in the flow and fluidization of Geldart Group C particles is their cohesive nature due to strong interparticle forces. The "nanoparticle modulation" technique is adopted to reduce the interparticle forces of Group C particles and thus significantly improve their flow and fluidization quality. Group C + particles, a new type of fine particles with drastically reduced or insignificant interparticle forces, are created using the nano-modulation technique. Fundamental studies provided a comprehensive understanding of the flow and fluidization quality of Group C + particles. Nano-modulation led to major enhancements to both the static and dynamic flowability of Group C + particles. Moreover, Group C + particles exhibited revolutionary advancements in fluidization, which enabled its pseudo-particulate fluidization over a wide range of operating gas velocities, up to 200–300% times that of bed expansion. The high bed expansion allows more gas to be retained in the bed and provides large volumes for gas-solid interfacial contact, thus promoting chemical reactions, especially gas phase catalytic reactions.